Experimental and numerical study of a broadly tunable fiber optical parametric oscillator - Muhammad Ghawas; Olivia Zurita-Miranda; Valerian Freysz; Eric Freysz (Results in Optics)
We present a tunable singly resonant fiber optical parametric oscillator (FOPO) based on a four-wave mixing process occurring in a 35cm-long single-mode photonic crystal fiber. This FOPO is synchronously pumped at a repetition rate of 61MHz by tunable picosecond pulses centered around 1030nm. It generates parametric picosecond signal pulses tunable from 770nm to 1000nm with a pump-to-signal conversion efficiency of up to 24.7%. Over this wide tuning range, increasing the pump power from 300mW to 1200mW enables a transition from narrow-bandwidth to broad-bandwidth parametric generation. We developed a numerical simulations that replicates key experimental observations. By operating the FOPO with a 184cm long single-mode photonic crystal fiber, we achieved a broad continuum of light extending from 750nm to 1550nm with 1W of pump power.